2018
DOI: 10.1007/s11695-018-3283-z
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Management Task Force of the European Association for the Study of Obesity Released “Practical Recommendations for the Post-Bariatric Surgery Medical Management”

Abstract: Bariatric patients may face specific clinical problems after surgery, and multidisciplinary long-term follow-up is usually provided in specialized centers. However, physicians, obstetricians, dieticians, nurses, clinical pharmacists, midwives, and physical therapists not specifically trained in bariatric medicine may encounter post-bariatric patients with specific problems in their professional activity. This creates a growing need for dissemination of first level knowledge in the management of bariatric patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0
19

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 4 publications
2
85
0
19
Order By: Relevance
“…Some studies observed that time to pregnancy after bariatric surgery, as well as pre-pregnancy weight loss, was associated with perinatal complications [21]. Therefore, several authors recommended to delay pregnancy for at least 12 to 18 month after bariatric operation as pregnancy within this catabolic time frame might lead to altered nutritional supply, and therefore triggering the development of SGA infants [22,23]. In contrast, others found no differences in neonatal birth weight and adverse pregnancy outcomes between women who conceived within the first postoperative year and those who conceived later [24].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies observed that time to pregnancy after bariatric surgery, as well as pre-pregnancy weight loss, was associated with perinatal complications [21]. Therefore, several authors recommended to delay pregnancy for at least 12 to 18 month after bariatric operation as pregnancy within this catabolic time frame might lead to altered nutritional supply, and therefore triggering the development of SGA infants [22,23]. In contrast, others found no differences in neonatal birth weight and adverse pregnancy outcomes between women who conceived within the first postoperative year and those who conceived later [24].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, bariatric surgery is the most efficient method of obesity treatment [12]. Many studies have shown that bariatric surgery not only helps patients achieve long-term weight loss but also removes obesity-related complications, including T2DM and high blood pressure [13][14][15][16]. It has been demonstrated that weight-loss by laparoscopic sleeve gastrectomy leads to a 40%-65% reduction in excess weight.…”
Section: Introductionmentioning
confidence: 99%
“…Although psychological evaluation is mandatory for most surgery programs, there are no clear guidelines about what that assessment must involve [6]. In addition, after the procedure, psychological counseling is often neglected, which may have an impact on weight variation and in the achievement of long-term goals in this group of patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, weight regain after BS can occur and therefore all efforts must be made in order to prevent such occurrence. Several factors can explain this, each of which has high interindividual variability [7,8].…”
Section: Introductionmentioning
confidence: 99%